REPLACEMENT OF MAIZE WITH GRADED LEVELS OF NOODLE WASTE IN COMMERCIAL DIET OF AFRICAN CATFISH - ADEROLU, A. Z; AARODE, O.O.; ADIGUN , A. (Nigerian Journal of Fisheries, 2011)
A study was conducted to determine the suitability of noodle waste as maize replacement in the diet of African catfish juvenile. Four experimental diets were formulated with noodle waste replacing maize at three graded levels (10, 15 and 20%) and the control was without noodle waste. A total of 120 African catfish juvenile (16.49 ± 0.03) were distributed in ten fish per experimental tank (52.5 cm × 33.5 cm × 21 cm). The water was changed every two days and the feeding was done by hand to satiation twice daily. Diet 2 had the highest mean weight gain (P < 0.05) (92.69 ± 3.39 g) among the entire group. Similar pattern was observed in specific growth rate. The least significant (P < 0.05) feed conversion ratio was recorded by diet 3(0.98 ± 0.09), the diet also recorded the best protein efficiency ratio (2.31 ± 0.20). The fish were fasted for 24 h to determine the haematological parameters. The PCV peaked (P < 0.05) at the inclusion of the test ingredient. However, no pattern was observed (P < 0.05) in the cholesterol and triglycerides. The carcass protein was highest (P < 0.05) in diet 2, likewise the ether extract. The best growth rate and nutrient utilization was achieved in diet 2.